Influence of values, Halalan-Tayyiban awareness, and attitudes on young muslim consumers’ intention to purchase halal cosmetic products - Sutono, . (2016)
Consumers have attached increasing importance to values of safety, health, environment and animal friendliness in the products they consume. Meanwhile, the wholesomeness concept of halal does not cover the Shariah requirement only, but also the sustainability concept of personal hygiene and public safety. This trend is shown by more consumer demand for value-based items such as products that are halal, natural and eco-friendly. However, discussions and empirical examination of these issues are limited. Therefore, this study attempts to explore the influence of type of values (self transcendence and conservation), halalan-tayyiban awareness, and attitudes on intention to purchase halal cosmetic products. The data was collected through a selfadministered questionnaire survey with purposive sampling on 560 Indonesian young Muslim consumers. The data was then analyzed using Structural Equation Modeling. Findings of the present study revealed that type of values (self transcendence and conservation), halalan-tayyiban awareness, and attitudes were all important predictors of intentions to purchase halal cosmetic products. Overall, the results of this study confirm applicability of the value-attitude-behavior model in the context of halal cosmetic purchasing. Self transcendence and conservation were found to be predictors of halalan-tayyiban awareness of cosmetic products. Halalan-tayyiban awareness of cosmetic products was found to influence attitude towards halal cosmetic products. The findings also revealed that halalan-tayyiban awareness of cosmetic products may have mediated partially the influence of conservation on attitude towards halal cosmetic products. Conclusively, the findings demonstrated that there was significant relationship between attitudes and purchase intention of halal cosmetic products. An important theoretical contribution of this study is extending the value-attitude-behavior model by exploring halalan-tayyiban awareness. This study recommends marketers to integrate the concept of halalan-tayyiban in their strategic marketing activities to increase consumers’ halalan-tayyiban awareness of halal business practices, which in turn may enhance the image of halal products. The present study also suggests manufacturers to implement the concept of halalan-tayyiban into the products they produce.